The angel and the three men - khan , Saniyasnain (India goodword kidz, 2011)
The Angel and the Three Men is a well-known story from a hadith of the Prophet Muhammad (PBUH). It teaches powerful lessons about gratitude, honesty, and being thankful to Allah.